Posttraumatic Stress Disorder and Nonadherence to Treatment in People Living With HIV: A Systematic Review and Meta-analysis - Hou, Jianhua; Fu, Jiangning; Meng, Siyan; Jiang, Taiyi; Guo, Caiping; Wu, Hao; Su, Bin; Zhang, Tong (Frontiers in Psychiatry, 2020)
Background: Posttraumatic stress disorder (PTSD) is a commonly reported and serious complication among people living with HIV (PLWH). PTSD may significantly increase unintentional non-adherence to antiretroviral therapy. In this systematic review and meta-analysis, we aimed to pool the observational studies exploring the association between PTSD and medication adherence among PLWH. Methods: Comprehensive searches were conducted in PubMed/Medline, Web of Science, PsycINFO, Google Scholar and ProQuest to identify relevant articles and dissertations. A random effects meta-analysis with inverse variance weighting was used to summarize the odds ratio (OR) across studies. Meta-regression and subgroup analyses were also carried out to assess the moderation effects for potential factors. Results: By synthesizing 12 studies comprising 2489 participants, the pooled odd ratio of non-adherence to antiretroviral therapy was 1.19 (95%CI (Confidential Interval) 1.03-1.37, p=0.02). No significant publication bias was detected by Egger’s test (Intercept=0.842, p=0.284). Factors moderating the association were mean age of participants, depression adjustment and depression (all p<0.05). Conclusions: This meta-analysis supports that PTSD is related to adherence in PLWH. The hypothesized mechanisms (avoidant behavior and cognitive impairment) underlying this association need further investigation. Overall, this study highlights that clinicians should thoughtfully integrate timely mental health intervention into routine care.